2008
DOI: 10.2741/3090
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of endothelial Man and Gal-binding lectins in sensing the flow in coronary arteries

Abstract: The coronary endothelial luminal membrane (CELM) glycocalyx has diverse molecules involved in blood flow signal transduction. Evidence suggests that some of these structures may be lectinic. To test this, we synthesized two monosaccharide polymers (Mon-Pols) made of Mannose (Man-Pol) or Galactose (Gal-Pol) covalently coupled to Dextran (70 kDa) and used them as lectin affinity probes. In situ intracoronary infusion of both polymers resulted in CELM-binding but only Man-Pol caused a reduction in flow-induced po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…In four previous papers we have reliably isolated the whole protein fraction from the coronary luminal endothelial surface membrane and glycocalyx thanks to the method developed and refined by different groups [8,12,14,26,29,30]. This procedure consists of coating of luminal endothelial membrane proteins with cationic colloidal silica particles (20-to 50-nm diameters) due to strong electrical binding to glycocalyx anionic proteins and polymerizing luminal endothelial membrane protein-bound silica with an anionic polymer.…”
Section: Isolation Of Luminal Endothelial Membrane Protein Fractionmentioning
confidence: 99%
See 4 more Smart Citations
“…In four previous papers we have reliably isolated the whole protein fraction from the coronary luminal endothelial surface membrane and glycocalyx thanks to the method developed and refined by different groups [8,12,14,26,29,30]. This procedure consists of coating of luminal endothelial membrane proteins with cationic colloidal silica particles (20-to 50-nm diameters) due to strong electrical binding to glycocalyx anionic proteins and polymerizing luminal endothelial membrane protein-bound silica with an anionic polymer.…”
Section: Isolation Of Luminal Endothelial Membrane Protein Fractionmentioning
confidence: 99%
“…Oligosaccharide polymer pretreatment: Our previous confocal microscopic and functional studies have shown that oligosaccharide polymers (a combination of mannose, galactose, and N-acetylglucosamine covalently bound to dextran) bind irreversibly with a high affinity to endothelial surface layer structures and, once bound, are not washed away [8,16,12,26]. As described above, control concentration-response curves to bradykinin were obtained at 11 ml/ min (basal pressure 51.1 ± 2.9 mmHg) and at 16 ml/min (basal pressure 81.2 ± 4.1 mmHg).…”
Section: Groupmentioning
confidence: 99%
See 3 more Smart Citations